Detecting software aging of web servers with real-valued negative selection algorithm - Huan Yang; Yiwen Liang; Chengyu Tan; Jun Fu (2011 IEEE 3rd International Conference on Communication Software and Networks, 2011)
Long-running web server systems are prone to suffer from software aging, which result in increasing failure rate and/or degradation of their performance. To avoid this phenomenon, detection of web server aging becomes an important issue in web server maintenance. Existing technologies depending on aging samples succeed in detecting known web server aging, but failed to detect previously unseen aging because of the nondeterministic nature of the web server aging. In this paper, an immune-inspired real-valued negative selection algorithm, which only needs normal samples to perform anomaly detection, was proposed to distinguish web server aging (non-self) from normal state (self). The basis of the detection is aging causes exhaustion of system resources and performance degradation, namely performance deviation from the normal state. Since normal samples are much easier to acquire from running web server than aging samples, we believe this algorithm will improve the web server aging detection performance, especially of unknown ones.